Ferroptosis induction in host rice by endophyte OsiSh-2 is necessary for mutualism and disease resistance in symbiosis - Xiong, Xianqiu; Zeng, Jing; Ning, Qing; Liu, Heqin; Bu, Zhigang; Zhang, Xuan; Zeng, Jiarui; Zhuo, Rui; Cui, Kunpeng; Qin, Ziwei; Gao, Yan; Liu, Xuanming; et al. (Nature communications, 2024)
Ferroptosis is an iron-dependent cell death that was discovered recently. For beneficial microbes to establish mutualistic relationships with hosts, precisely controlled cell death in plant cells is necessary. However, whether ferroptosis is involved in the endophyte‒plant system is poorly understood. Here, we reported that endophytic Streptomyces hygroscopicus OsiSh-2, which established a sophisticated and beneficial interaction with host rice plants, caused ferroptotic cell death in rice characterized by ferroptosis- and immune-related markers. Treatments with ferroptosis inhibitors and inducers, different doses of OsiSh-2, and the siderophore synthesis-deficient mutant Δ cchH revealed that only moderate ferroptosis induced by endophytes is essential for the establishment of an optimal symbiont to enhance plant growth. Additionally, ferroptosis involved in a defence-primed state in rice, which contributed to improved resistance against rice blast disease. Overall, our study provides new insights into the mechanisms of endophyte‒plant interactions mediated by ferroptosis and suggests new directions for crop yield promotion. Ferroptosis is of great importance in plant immunity including microbe-plant interactions. Here, the authors unveil that a regulated ferroptosis process is involved in the mutualistic symbiosis and disease resistance of endophyte OsiSh-2 and host rice.